Anti-Soviet Resistance of the Lithuanian Academic Youth in the 1950s and 1960s... - Dabrovolskas, Audrius (Genocidas ir rezistencija, 2024)
The main subject of this article is the anti-Soviet resistance of Lithuanian academic youth in the 1950s and 1960s. The anti-Soviet resistance movement showed that young people in Lithuania did not accept Soviet authority. They defined the Soviet regime as an occupying power and fought for Lithuanian independence. This battle for independence was not conducted with arms and was both organised and non-organised. The main forms of organised anti-Soviet resistance in Lithuania were the formation of anti-Soviet organisations and groups; the distribution of patriotic leaflets; painting patriotic slogans on walls, doors, etc.; raising national flags; and marking national and religious celebrations. Both non-organised and organised resistance had moral issues however. If you agreed with the Soviet lifestyle and system, you had to compromise yourself. Youths could not cope with the propaganda and moral limitations that were instituted by the Soviet regime, and they tried to rebel by reaching for new Western music, fashion, and other art forms. The ever increasing symbols of Western culture in Soviet Lithuania were also forbidden and persecuted. The forms of youth resistance in Lithuania showed the reluctance of young people to support the Soviet regime and lifestyle. The most active members of academic youth in Lithuania participated in anti-Soviet campaigns and the Soviet government treated them as nationalists, anti-Soviet elements. Youngsters who distributed patriotic leaflets or painted patriotic slogans on walls were not frequently punished, but they and sometimes their parents were reprimanded by Soviet activists, Komsomol members. Generally young people were sentenced to a term in a concentration camp for attending anti-Soviet organisations or groups. These punishments were strict and the mark of a previous conviction existed in the file of a person throughout the entire period of the Soviet occupation. This black mark in one’s file created complexity in one’s life in Soviet Lithuania and often conflict with society. The anti-Soviet resistance of Lithuanian academic youth in the 1950s and 1960s was inherent from all Lithuanian people anti-Soviet resistance. Many young people were sentenced for being anti-Soviet, but the most rebellious never relinquished their patriotism or fight for freedom. This unarmed fight for freedom in the 1950s and 1960s made the largest influence on further struggles in the 1970s and 1980s till the independence of Lithuania was re-established.
Keywords: Lithuania; Soviet occupation; anti-Soviet resistance; academic youth resistance